Characterization and function study of a glutamyl endopeptidase homolog from Nocardia seriolae. Issue 6 (27th November 2020) - Wang, Wenji; Hou, Suying; Chen, Guoquan; Xia, Liqun; Chen, Jianlin; Wang, Zhiwen; Lu, Yishan
Abstract: Glutamic endopeptidases (Glu), belonging to the class of serine proteases, are a subfamily of chymotrypsin‐like proteolytic enzymes, which are regarded as important virulence factors in bacteria. However, the roles of glutamic endopeptidases of Nocardia seriolae in pathogenic process still remain uncertain. Here, a glutamic endopeptidase homolog from N. seriolae (GluNS) was cloned and its function was elucidated. GluNS encoded a 414‐aa protein which shared 93% identity to N. concava . In the phylogenetic tree, the glutamic endopeptidases of genus Nocardia clustered together firstly and then clustered with Streptomyces species. Moreover, GluNS was identified to be a secreted protein of N. seriolae and localized in the mitochondria of FHM cells. The transient overexpression of GluNS significantly induced increase in caspase‐3 activity and decrease in ΔΨm values in FHM cells. The number of apoptotic bodies was remarkably higher than that in control group. Taken together, GluNS overexpression induced apoptotic characteristics in FHM cells. This study provided new insights into the function of glutamic endopeptidase from N. seriolae .